Minimum Inhibitory Concentration of Zataria multiflora Boiss. Essential Oil on Sallmonella enteritidis, Listeria monocytogenes, Escherichia coli 0157: H7 and Staphylococcus aureus - Ghasemi, Sara; Haji Seyed Javadi, Nasrin; Esmaeili, Somayeh; Khosravi-Darani, Kianoush (Asian Journal of Chemistry, 2012)
The objective of this study was to determine the minimum inhibitory concentration of the essential oil of Zataria multiflora Boiss. in inhibiting Salmonella enteritidis, Listeria monocytogenes, Escherichia coli 0157: H7 and Staphylococcus aureus. The essential oil of Zataria multiflora was extracted with a Clevenger-type apparatus using hydro-distillation method for 2 h. The effect of Zataria multiflora's essential oil on growth of mentioned pathogens were determined by using microtiter plate. The minimum inhibitory concentration of Zataria multiflora Boiss. for S. enteritidis and E. coli were enumerated at 6250 ppm. The minimum inhibitory concentration of antimicrobial agent for L. monocytogenes and St. aureus were found at 3125 ppm.